DEVELOPING POSITIVE IMAGINATION IN EARLY CHILDHOOD - Chairilsyah, Daviq (UIR Press, 2021)
ABSTRACT So naturally, the early childhood brain develops an imaginary world of imagination. An imagination that is directed to positive things will certainly foster thoughts and give a child enthusiasm in life at home and school. The paradigm that occurs in society is that imagination in children is always associated with negative and useless, even dangerous things by saying that a child is insane if he has imagination in his life. It is a tool for generating creative and useful ideas. This paper uses a literature study method. Increasing a positive imagination in children is necessary so that the role of teachers and parents is needed to cultivate and direct this imagination in children into creative and useful ideas. Teachers are playing a part in improving the number of play tools in children, engaging children to take walks, inviting children to tell stories, providing a safe and free atmosphere to help develop children's positive imaginations in school. Meanwhile, the role of parents in the family environment is to provide a safe and free-wheeling atmosphere, do not prohibit children too much, invite them to listen to classical music, and base all thoughts on religion.